Southern First Ladies : Culture and Place in White House History - Sibley, Katherine A. S. (Katherine Amelia Siobhan), 1961- (Book collections on Project MUSE., 2020)
"The American South has long been understood to have a strong sense of place, as seen especially in the arts. This distinctive Southern culture has also had an important influence on the American first ladies, though scholars have largely overlooked the region's role in shaping their legacy. Through nineteen biographical and thematic chapters, Southern First Ladies explores how the cultural background of the Southern first ladies shaped their priorities and responsibilities. With four of the first five presidents from the South, their partners played an important role in the earliest definition and development of what it has meant to be first lady, especially in the ways they wrestled with the traditions of their backgrounds and responded to often confining social expectations. Part one of the volume surveys the Southern first ladies from the Early Republic to the late Reconstruction period. Martha Washington, Dolley Madison, Elizabeth Kortright Monroe, and Julia Tyler defined the Southern first lady, instituting and reinforcing Southern practices and prejudices, especially regarding gender, race, and the institution of slavery. These practices violently tore the country apart during the Civil War, which the book explores by looking at the complex, polarizing figures of Mary Lincoln and Varina Davis. Nancy Beck Young concludes the first part by focusing on the Southern roots of the activism that has come to characterize this office. Part two then examines the activist first ladies of the twentieth and twenty-first centuries, including the Progressive era first ladies, Ellen and Edith Wilson, the environmentally focused Lady Bird Johnson, and the diplomacy of Rosalynn Carter. The authors also look at those who migrated to the South, such as Barbara Bush and Hillary Clinton. Katherine Sibley concludes the volume by reflecting on the activism of the modern first ladies"--